2013
DOI: 10.4236/fns.2013.48113
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of <i>Gingo biloba</i> Extract on Carbendazim-Induced Hepatotoxicity in Albino Rats

Abstract: Carbendazim is a broad spectrum carbamate fungicide used in the control of various fungal pathogens. The present work studied the effect of carbendazim on the liver of albino rats and the possible protective role of Ginko biloba extract (EGB). Liver of carbendazim-treated animals showed histopathological and histochemical alterations. The histopathological changes include hepatic tissue impairment, cytoplasmic vacuolization of the hepatocytes, and congestion of blood vessels, leucocytic infiltrations and fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Also, it induced degeneration of proximal tubules' epithelial cells [60,61]. In the present study, co-administration of GBE and/or Mel in combination with BPA revealed remarkable improvement in the liver and kidney tissues compared to BPA-treated group [62]. They demonstrated that the histopathological score of fibrosis together with liver function were improved in rats treated with CCl 4 plus GBE.…”
supporting
confidence: 51%
“…Also, it induced degeneration of proximal tubules' epithelial cells [60,61]. In the present study, co-administration of GBE and/or Mel in combination with BPA revealed remarkable improvement in the liver and kidney tissues compared to BPA-treated group [62]. They demonstrated that the histopathological score of fibrosis together with liver function were improved in rats treated with CCl 4 plus GBE.…”
supporting
confidence: 51%
“…Various plants and their oils have been previously used to treat the toxicity of CBZ on animals, such as olive ( Olea europaea) leaves Zari and Al-Attar, (2011) , licorice ( Glycyrrhiza glabra ), Fenugreek ( Trigonella foenum-graecum Linn .) seeds extract Lamfon (2012) , Gingo bilola extract Mahboub and Lamfon, (2013) , Ginger ( Zingiber officinale ) Salihu et al (2016) , Jaft internal layer of Quercus brantii Mirzaei et al (2015) , Nigella sativa oil Hashem et al (2018) , Quercetin Abou Zaid et al (2018) , Nigella sativa and Foeniculum vulgar seeds extracts Alghamdi, (2020) , Vitamin C ( Lalhriatpuia et al, 2021 , Kiran, 2022 ), and banana peel ( Abdel-Rahman et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chemicals: Acrylamide (ACR) from Sigma Chemical Company was made just before usage by dissolving it in distilled water [9] . It was purchased by Amriya Company (Egypt) for Pharmaceutical Industries under license from Beaufour Ipsen International, Paris, France [10] . GB extract was used as Tanakan 761 (EGB).…”
Section: Methodsmentioning
confidence: 99%